Contextual Factors Which Affect the Success of Microcredit Programs Among Women in Ghana. Issue 2 (June 2020) - Afriyie, Kwadwo; Ganle, John Kuumuori; Segbefia, Alexander Yao; Kamau, Pauline; Wamue-Ngare, Grace
Microcredit programs usually target poor rural women to reduce poverty and empower the women involved. The general body of existing research provides conflicting evidence, depending on context, poverty reduction and empowerment may or may not be partially achieved. Research on the effects of context on microcredit is limited in Ghana. Based on focus group discussions and in-depth interviews with stakeholders, the contextual factors that affect microcredit for poverty reduction among women are explored. The findings of this study suggest that the orthodox use of social collateral through group lending doesn't fully account for why some microlending programs are effective, and others are not. Contextual factors appear to make the difference.